The Effect of Fraud Pentagon on Fraudulent Financial Reporting - Hanna Nihayah Fahira; Margo Purnomo; Mas Rasmini (Integrated Journal of Business and Economics (IJBE), 2021)
The purpose of this research is to demonstrate and investigate the influence of the fraud pentagon on fraudulent financial reporting. A quantitative technique was applied in the investigation. This study makes use of secondary data and a purposive sampling technique. The sample for this study consisted of 31 Property and Real Estate Sub-Sector Service Companies that were listed on the IDX from 2017 to 2019. Regression analysis of panel data was employed as the statistical strategy in this investigation. The findings show that the pressure and opportunity variables have a positive and significant impact on fraudulent financial reporting. Meanwhile, rasionalization, competence, and arrogance all have a negative and minor impact on fraudulent financial reporting. This study, on the other hand, shows that pressure, opportunity, rationalization, competence, and arrogance all have an impact on dishonest financial reportingKeywords:  Pressure,Opportunity,Rasionalization,Competence,Arrogance